Old and high : a guide to understanding the neuroscience and psychotherapeutic treatment of baby-boom adults' substance use, abuse, and misuse - Youdin, Robert (New York : Oxford University Press, 2019)
" Despite the stereotype of older adults primarily abusing alcohol, clinical practice insights indicate that the baby-boom generation frequently abuses the same substances as younger adults--including alcohol, opioids, benzodiazepines/z-drugs, neurostimulants, cannabis, and tobacco/nicotine. Old and High exposes this hidden epidemic and emphasizes the importance of understanding psychotropic substance abuse as a community health problem. Further, the book identifies the unique cultural values, social values, and risks that baby-boom adults have with respect to substance abuse and misuse to give students and clinical professionals in psychology, social work, gerontology, nursing, and medicine a foundation for working with this population. Readers will, specifically, learn how to integrate current neuroscience findings with contemporary psychotherapy techniques and harm-reductive interventions to help older adults achieve successful recovery from substance abuse problems. Considering that we will likely observe an increase in rates of substance abuse as the baby-boom generation continues to age--and live longer than previous groups--there will be a major need to better understand the unique risk factors and treatment approaches when working with older adults. "--
"Old & High addresses unmet mental health needs of older adults experiencing psychotropic substance dependence. It provides insight for clinical professionals in psychology, social work, gerontology, nursing, and medicine on how to integrate current neuroscience findings with contemporary psychotherapy techniques and harm reductive interventions to help older adults achieve successful recovery from substance abuse problems. Extensive use of clinical vignettes brings a humanistic perspective to the academic, evidenced-based research presented"--
Includes bibliographical references and index.
Keywords: Older people -- Drug use -- United States; Older people -- Alcohol use -- United States; Baby boom generation -- United States; Psychotropic drugs -- United States; Alcoholism -- Treatment -- United States; Neurosciences -- United States; SOCIAL SCIENCE / Gerontology